A career on the Hungarian-Ottoman frontier in the late 15th century. Despot Vuk Grgurević as the Ban of Jajce - Obradović, Nenad (Historical Thought, 2024)
On the following pages the goal is to present activities and duties of Hungarian border officials in the context of border society, and to describe the role of Serbian despot Vuk Grgurević as ban of Jajce, which he performed near the end of his life. If our assumptions in correct, it is possible to prolong period of his service also to the years after 1481, as is it had been considered until now in historical literature. This conclusion is supported by the fact that he acted as a mediator in diplomatic negotiations. In addition, it is not unfounded to assume that the famous warrior stayed in this position until his death in 1485, as evidenced by the fact that next ban of Jajce is not mentioned in known sources until 1486, and also folk tradition remembers the despot Vuk as Jajčanin (i.e. a man from Jajce).